Dependence of Syngas Composition on Microstructure of La0.8Sr0.2Cr0.5Mn0.5O3–δ Based Cathode for CO2 and H2O Co-Electrolysis. (30th May 2017) - Maide, Martin; Lillmaa, Kadi; Nurk, Gunnar; Lust, Enn
Abstract : In this study, catalytically active nickel catalyst was grown via redox exsolution on the surface of A-site deficient La1-x Srx Cr1-y Mny O3-δ based electrode with 6 % of Ni on B-site impregnated onto porous matrix made from Sc0.1 Ce0.01 Zr0.89 O2- δ . Influence of A site deficiency on the electrochemical performance and effect of conditions of electrolysis and nanocatalyst properties on the outlet gas composition were studied.